2019
DOI: 10.1108/ajim-07-2018-0181
|View full text |Cite
|
Sign up to set email alerts
|

Understanding credibility judgements for web search snippets

Abstract: Purpose It is well known that information behaviour can be biased in countless ways and that users of web search engines have difficulty in assessing the credibility of results. Yet, little is known about how search engine result page (SERP) listings are used to judge credibility and in which if any way such judgements are biased. The paper aims to discuss these issues. Design/methodology/approach Two studies are presented. The first collects data by means of a controlled, web-based user study (N=105). Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Other researches focused on determining how the search engine result page (SERP) listings are used to determine credibility through user studies [22]. More specifically, several studies have been conducted related to assessing the credibility of health-related content on the web.…”
Section: Related Workmentioning
confidence: 99%
“…Other researches focused on determining how the search engine result page (SERP) listings are used to determine credibility through user studies [22]. More specifically, several studies have been conducted related to assessing the credibility of health-related content on the web.…”
Section: Related Workmentioning
confidence: 99%
“…Web search snippets in terms of quality evaluation are subject to credibility judgments. The same short snippets provide diverse informational cues and how these cues can be interpreted differently depending on the user and his or her background [25]. Snippets have different levels of readability and word complexity, however readability of snippets in Google and Bing search engines mismatched with the reading comprehension of children age 11 to 13 [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Varying relatively few words, and even their location, within a snippet can have a significant influence on the clickthrough of a snippet [31]. Normal snippets in previous works have mainly been evaluated as being informative enough for users of web search engines [25]. Recent research has been conducted on different age groups to see how normal snippets are perceived by younger and older search engine users [26].…”
Section: A Normal Snippetsmentioning
confidence: 99%
“…For last few years it has been observed that some tests of changing length of regular snippets either on desktop or on mobile version have been done [4,5]. Research interest for regular snippets is about their function of being enough informative for users [6]. Recent research were conducted on different age groups to determine how regular snippets are perceived by younger or older search engine users [7].…”
Section: Literature Reviewmentioning
confidence: 99%